2020
DOI: 10.1007/s11146-020-09798-x
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive Reuse of Religious Heritage and Its Impact on House Prices

Abstract: Due to social demographic change and secularization, religious heritage sites in Europe are on the verge of losing their original functions. While the adaptive reuse seems to be a proactive strategy to preserve the historical and cultural value embedded in religious heritage sites, little is known concerning its external impact. This paper aims to fill this gap by investigating the external effect of reusing religious heritage on surrounding house prices. Employing both the parametric and non-parametric differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 30 publications
0
8
0
Order By: Relevance
“…The preservation of heritage or landmarks has been found to lead to a price premium of nearby property by 1.7%, 1.4%, and 0.5% within a radius of 50 m, 100 m, and 200 m [12]. Liu and Liu [56] plot the irregular curve of average property prices close to the heritage adaptive reuse projects.…”
Section: The Correlation Between Urban Regeneration Characteristics A...mentioning
confidence: 99%
“…The preservation of heritage or landmarks has been found to lead to a price premium of nearby property by 1.7%, 1.4%, and 0.5% within a radius of 50 m, 100 m, and 200 m [12]. Liu and Liu [56] plot the irregular curve of average property prices close to the heritage adaptive reuse projects.…”
Section: The Correlation Between Urban Regeneration Characteristics A...mentioning
confidence: 99%
“…Moreover, in order to stabilize the development of the real estate market, China has issued a series of strict macro-control policies. Some income sources of real estate have been cut off in that way, and the real estate market is facing overwhelming pressure [10]. In addition, ascribed to changes in consumption conception, the new generation is more inclined to rent a house.…”
Section: Threatsmentioning
confidence: 99%
“…Last, but not least, is the issue related to the gentrification phenomenon that these interventions may generate [42,43]. Often, the increase in real estate values brought about by these processes can lead to depopulation or a decrease in the population living in the area [44].…”
Section: Estimation Of the Impact Of Adaptive Reuse Projects On The H...mentioning
confidence: 99%
“…Several authors have demonstrated that residents value the functional, cultural, or aesthetic significance of these services, infrastructures, and heritages, increasing the demand for living space and property values in these markets; many studies have been conducted to investigate the impact of urban green infrastructure [51][52][53][54], modes of transportation [55][56][57], and historic cultural heritage proximity [58,59], but the impact of reused cultural heritage has received little attention (Table 1). Indeed, while adaptive reuse appears to be a proactive strategy for preserving the historical and cultural value embedded in heritage sites, little is known about its external impact [44]. Iftekhar et al [60] used the HPM and the discrete choice experiment technique to understand the benefits of improving the Main Outfall Sewer reserve in Melbourne, Australia, and assess residents' preferences for different large-scale, water-sensitive urban improvement options for a disused historic site.…”
Section: Estimation Of the Impact Of Adaptive Reuse Projects On The H...mentioning
confidence: 99%
See 1 more Smart Citation